PEMBERDAYAAN KELUARGA DALAM PENANGANAN PERTAMA KASUS TERSENGAT LISTRIK PADA ANAK DI DESA MLAJAH - Heni Ekawati (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2019)
Electric shock is one of the emergencies in children that often occurs because the power source tends to be easily accessible by children. When the baby / child touches an electric current, with the hands, feet or mouth, an electric current flows through the body parts. According to the National Fire Protection Association, about 2,400 children suffered severe trauma and burns from electric shocks because they pushed their hands into the power outlet plugs. The incidence of burns from electric shock accounts for about 2-3% of all burns in children requiring emergency care. In addition, in Indonesia, around 12 children die from electricity each year. Based on a survey through interviews with parents of children in Mlajah Village, it was found that many parents of children in Mlajah Village did not know about the first handling of cases of electric shock. The method used to carry out community service is by collecting data on the number of parents who have children in Mlajah Bangkalan Village, then conducting interviews with mothers about the understanding of being electrocuted in children and first handling of being electrocuted in children, then making a time contract with the mother. The activity was continued with training on the first handling of an electric shock on a child which was held at the Mlajah Bangkalan Village Hall. The participants of the activity were 30 mothers in Mlajah Village who participated in the training for the first handling of an electric shock to a child. While participating in the activity, the mother was very enthusiastic about the material presented. She was also able to demonstrate how to remove objects that caused electric shocks. Also, mothers also understand the concept of electric shock and its first treatment.